2017
DOI: 10.1007/s00421-017-3713-y
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of size and echo intensity of abdominal skeletal muscles using extended field-of-view ultrasound imaging

Abstract: The present results indicate that EFOV ultrasound imaging has high repeatability for measuring CSA and echo intensity of abdominal skeletal muscle groups in healthy college-aged males.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 25 publications
3
26
2
Order By: Relevance
“…Previous studies have reported that there is a significant negative association between MT and EI on quadriceps femoris in healthy older adults 19,29 ) . A previous study of acute stroke patients by Maeda et al reported a significant negative association between MT and EI of the quadriceps femoris 30) .…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Previous studies have reported that there is a significant negative association between MT and EI on quadriceps femoris in healthy older adults 19,29 ) . A previous study of acute stroke patients by Maeda et al reported a significant negative association between MT and EI of the quadriceps femoris 30) .…”
Section: Discussionmentioning
confidence: 84%
“…EI of individual pixels was expressed as a value between 0 (black) and 255 (white) by 8-bit grayscale, and the mean EI value of each pixel in the region of interest was obtained. Reliability of MT and EI measurements has been established, with intraclass correlation coefficient (ICC) values in the range of 0.90-1.00 for MT and 0.77-0.95 for EI [17][18][19][20][21] . To examine the reliability of our measurements, an ultrasound image of each muscle was obtained on two separate days in eight healthy subjects in another sample of this study.…”
Section: Ultrasound Measurementmentioning
confidence: 99%
“…To our knowledge, this is the first study to examine the reliability of EFOV US in the assessment of RA thickness and length. Tanaka et al [27] reported excellent reliability in measuring the RA cross-sectional area (ICC values ranged from 0.944 to 0.958) and echo intensity (0.851 to 0.945) using EFOV US. Further, Keshwani et al [31] examined the inter recti distance (IRD) of RA in postpartum women and found that images acquired using EFOV techniques were highly correlated with those acquired using conventional imaging (r>0.95, p<0.001).…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of US evaluation is that it permits observation of only a limited region of the muscle of interest and thus, long muscles like the RA, require multiple measurements in different segments. Extended field-of-view (EFOV) US overcomes this limitation as it allows the scanning of entire tissue areas within one continuous scan [26] with high reliability [27]. For the RA muscle, EFOV US can assist in visualizing the distance between tendinous inscriptions, thus proving an estimate of the amount of RA shortening from rest to contraction.…”
Section: Introductionmentioning
confidence: 99%
“…The stitching is often limited by the lack of clarity of the original image and the lack of accuracy of image matching, resulting in poor results. [11], [12]. So we propose Dual-enhanced EFOV-US method which can reduce noise interference and enhance the resolution of the image, thus improving the quality of the ultrasound wide-range image.…”
Section: Introductionmentioning
confidence: 99%